Grain Yield and Nutrient Uptake of Rice (Oryza sativa L.) Cultivars in Competition with Barnyardgrass [Echinochloa crus-galli (L.) P. Beauv.] [RESEARCH NOTE] - Aminpanah, Hashem (2012)
An experiment was conducted in plastic pots at the Rice Research Station in Tonekabon, Iran to determine the extent of variation between two rice cultivars, in terms of yield/biomass production and nutrient uptake in competition with barnyardgrass (BYG) through a replacement series study. The experiment was carried out in a randomized complete block design with a factorial treatment arrangement and three replications. The factors were two rice cultivars (Shiroodi and Khazar) and five rice:BYG plant ratios (8:0, 6:2, 4:4, 6:2 and 0:8). Replacement series diagrams for aboveground dry weight and grain yield illustrated that Shiroodi was more competitive than BYG, while Khazar was less competitive than BYG. The aboveground dry weight and grain yield of Khazar were significantly reduced with increasing rice:BYG ratio but significantly increased in Shiroodi. Grain, stem and leaf nitrogen (N) uptakes in Shiroodi, unlike in Khazar, significantly increased with decreasing rice:BYG ratio. On the other hand, Khazar had lower grain and leaf N uptake than Shiroodi at all rice:BYG ratios. Grain P uptake for Shiroodi, unlike in Khazar, significantly increased at 4:4 and 2:6 rice:BYG ratios. Grain, stem and leaf K uptake in Shiroodi increased significantly as the BYG population increased from 0 to 6 plants per pot, while BYG competition did not significantly reduce the grain, stem and leaf K uptake in Khazar cultivar. Moreover, Khazar had less grain K uptake than Shiroodi at all rice:BYG ratios. This study demonstrated the differential response of rice cultivars in competition with BYG in terms of grain yield and nutrient uptake.
Keywords: Rice yields